ANALISIS DATA POLITIKUS MENGGUNAKAN NODE2VEC DAN ALGORITMA HARMONIC CENTRALITY - Erizkika Mochammad Arsy Rofi; Nur Aini Rakhmawat; Ahmad Rifqy Syarwani (UNIVERSITAS STEKOM, 2020)
AbstractIndonesia is a democratic country with political party acting as people voices. Politician acquiregovernmental position through affiliation with a political party. The political party voices can influenceother parties and the whole political system. Hence, measuring the influence of a political party is done todetermine the impact in the government system. Using harmonic centrality algorithm to measure theinfluence of a political party or politician which facilitated by Node2Vec. Analysis results shows that thereis a political party that has the most influence in the government. However the graph has quite low densitydue to data limitation.Keywords: harmonic centrality, node2vec, politician, graph analysis